2014
DOI: 10.1002/aenm.201400867
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Stable Organic Electrolyte for the Lithium Oxygen Battery

Abstract: mass of both reactants and a favorable 3.0 V potential. [3][4][5][6] The theoretical specifi c energy of 3505 Wh kg -1 , and energy density of 3435 Wh L -1 (based on Li 2 O 2 ), is very attractive compared to contemporary Li-ion couples that are calculated to have theoretical values near 400 Wh kg -1 and 1400 Wh L -1 . Practical values for Li-air batteries are estimated near 1000 Wh kg -1 , [ 7 ] which compare favorably to current Li-ion commercial cells (210 Wh kg -1 ), but realizing this specifi c energy ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
233
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(261 citation statements)
references
References 62 publications
15
233
0
8
Order By: Relevance
“…[7,9] Thec ategorization based on the various decomposition pathways as summarized above is new.T he knowledge presented here is not limited to the reactive oxygen species,but also applicable to other radicals or anions that might exist in the system, such as redox mediators,d issolution of metal catalysts or electrolyte decomposition intermediates.T of acilitate the understanding of the systems,wefurther list different discussions in Table 1, where the mechanisms and chemical structures are correlated for easy reading.These efforts provide us with new insight into the role of oxygen species on the decomposition of the electrolytes.I ti sc onceivable that ethers can be stabilized by the substitution of the Honthe carbon backbone with inert groups such as -CH 3 .T his hypothesis has been recently verified by experimental efforts by Nazar et al [20] Similarly,the methylation of b positions on PYR cation may improve the stability of the related ionic liquid cation. Nevertheless,t he synthesis and purification of modified electrolytes may incur high cost, which can be an issue for practical applications.I na ddition, the introduction of bulky substitution groups may decrease the oxygen diffusivity, leading to high overpotentials.…”
Section: Summary Of Electrolyte Decomposition and Outlook Of Future Ementioning
confidence: 79%
See 3 more Smart Citations
“…[7,9] Thec ategorization based on the various decomposition pathways as summarized above is new.T he knowledge presented here is not limited to the reactive oxygen species,but also applicable to other radicals or anions that might exist in the system, such as redox mediators,d issolution of metal catalysts or electrolyte decomposition intermediates.T of acilitate the understanding of the systems,wefurther list different discussions in Table 1, where the mechanisms and chemical structures are correlated for easy reading.These efforts provide us with new insight into the role of oxygen species on the decomposition of the electrolytes.I ti sc onceivable that ethers can be stabilized by the substitution of the Honthe carbon backbone with inert groups such as -CH 3 .T his hypothesis has been recently verified by experimental efforts by Nazar et al [20] Similarly,the methylation of b positions on PYR cation may improve the stability of the related ionic liquid cation. Nevertheless,t he synthesis and purification of modified electrolytes may incur high cost, which can be an issue for practical applications.I na ddition, the introduction of bulky substitution groups may decrease the oxygen diffusivity, leading to high overpotentials.…”
Section: Summary Of Electrolyte Decomposition and Outlook Of Future Ementioning
confidence: 79%
“…[41] Their reactivity toward auto-oxidation, [20] nevertheless,p resents significant problems ( Figure 1). For example,t he a-H in ethers has been shown reactive toward superoxide radicals.…”
Section: The Role Of Oxygen Species In Auto-oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…The slightly higher yields indicate that the relatively high surface area of the Li 2 O 2 film that grows on the electrode in the absence of DBBQ leads to more decomposition of the electrolyte solution than is the case for the large particles in solution. It has also been suggested that LiO 2 is responsible for solvent decomposition on discharge 26,41,42 and, as discussed below, our analysis points to a mechanism that avoids this reactive intermediate. Attempts to charge the cells after discharge proved fruitless (see Supplementary Fig.…”
Section: Cyclic Voltammetry Studies With Dbbqmentioning
confidence: 81%